Factors of Global Competitiveness of American LNG - S. V. Zhukov (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2019)
The United States started lique fied natural gas (LNG) export in 2016 and just in two years became the world’s fourth largest exporter of LNG. There is a high probability that in the near future the U.S. will emerge as the third largest LNG exporter after Australia and Qatar. The article focuses on the factors, which ensure global competitiveness of U.S. LNG until 2030. The authors show that: first, the first wave of American export LNG projects significantly speeded up restructuring of contract system in the world gas trade as well as suppor ted development of a more flexible mechanism of natural gas pricing; secondly, production costs of the associated natural gas in the U.S. are relatively low and it is highly probable to expect Henry hub gas price to stabilize at around 2.5 dollars per MMBTU in the long run, what gives the American gas producers potential capability to significantly improve their global competitiveness by means of production and transportation costs reduction; fourthly, new waves of U.S. LNG export will not necessa rily be linked to the Henry Hub index, but to a wide range of price indicators, inclu ding the Brent oil price. With increasing flows of globally competitive Ameri can LNG entering the market, transformation of the institutional structure, contracts system and price mecha nism that have been unfold in the world LNG trade for the last ten to fifteen years became irreversible. That creates prerequisites for rapid formation of the world LNG market as well as with a some time lag of a global gas market.